NETIZEN COMMENTS ON PRESIDENT JOKO WIDODO’S INSTAGRAM POST: A CRITICAL DISCOURSE ANALYSIS - Syifa, Nurbani; Hidayat, Didin Nuruddin (Jurnal Ilmiah Aquinas, 2020)
Social criticism is one form of communication in the society that aims or functions as a control of the course of a system or process of society. Instagram has been perceived as one of the most popular social media today. One of the focuses of this research is on one of the photos that President Joko Widodo brought up in his Instagram account. The study aims to examine how the form of social criticism delivered by netizens made in the comments column uploaded by President Joko Widodo. This study employed a qualitative approach to analysis. The data analysis technique used in this study was based on the theory put forward by Teun A Van Dijk’s Critical Social Discourse Analysis. The results of this study found the the background and knowledge of social netizens regarding Jokowi's presidential in the vocabularies of the comments they wrote, and their comments that stimulated other comments from other netizens.